Exploiting the Arabic Wikipedia for semi-automatic construction of a lexical ontology. (1st January 2013) - Boudabous, Mohamed Mahdi; Belguith, Lamia Hadrich; Sadat, Fatiha
In this paper, we propose a hybrid (numerical/linguistic) method to build a lexical ontology for the Arabic language. This method is based on the Arabic Wikipedia. It consists of two phases: analysing the description section in order to build core ontology and then using the physical structure of Wikipedia articles (info-boxes, category pages and redirect links) and their contents for enriching the core ontology. The building phase of the core ontology is implemented via the TBAO system. The obtained core ontology contains more than 200, 000 concepts.